Ecological Spatial Model of Maize (Zea Mays L.) In Wanggarasi Sub-District, Pohuwato Regency – Gorontalo Province, Indonesia - Fitria S. Bagu; Zulzain Ilahude; Nurmi Hafid; Wawan Pembengo (International Journal of Technology and Education Research, 2025)
This research was conducted in Wanggarasi Sub-district, Pohuwato Regency, Gorontalo Province, specifically in Bohusami Village and Bukit Harapan Village. The objectives of this study were (1). To analyze the biophysical land conditions (land capability, land suitability, land carrying capacity, production), as well as the social conditions of the community, particularly population pressure, which can support a sustainable maize land-use system. (2). To develop an appropriate model for optimizing sustainable maize cultivation in Wanggarasi Sub-district, Pohuwato Regency, Gorontalo Province. The method used was land evaluation with a land unit approach. Sampling locations were determined using stratified random sampling, considering land units at the study sites—namely, slope, landform, and land use. The preparation of land capability maps, land suitability maps, and land optimization maps was carried out through interpretation of RBI maps, administrative maps, land unit maps, and LCLP analysis results. Meanwhile, maps of land carrying capacity, population pressure, and production were developed based on RBI maps, administrative maps, and secondary data. Data analysis was conducted using ecological spatial analysis with Geographic Information System (GIS) and supporting socio-economic data were analyzed descriptively. The research results showed that the study area is dominated by land with low optimization categories (R), expressed through the functional formula: OPT (R) = f (KL (III, IV) + KS (S3, N1) + DDL(R) + P(R) + TP(R)). The models and strategies for optimizing land in the low category (R) can be implemented through: (1) Identifying land units combining dry fields and rainfed areas that ensure the availability of land with high (T) or moderate (S) optimization categories, with a minimum area approximately equal to that of land units categorized as moderate or low in the sub-district. (2) Identifying land-use combinations that can yield production categorized as high (T) or moderate (S) land optimization by converting part of the coconut plantation area—particularly those needing replanting—into dryland maize cultivation. Additionally, seeking land-use combinations that ensure the availability of land areas with moderate optimization category (S), such as mixed gardens and dry fields.